Optimalisasi Media Digital untuk Promosi Pendidikan di SD Negeri Kedawung 2, Kuripan – Probolinggo - Sudirman; Misbahul Arifin; Layli Rohmatillah (JDP (JURNAL DINAMIKA PENDIDIKAN), 2025)
This study aims to examine the optimization of digital media as a means of promoting education within public schools, specifically at SD Negeri Kedawung II Kuripan Probolinggo. In today’s digital era, social media and other digital platforms have become strategic tools for building the image and communication of educational institutions to the wider public. The research employs a descriptive qualitative approach with a case study method, involving data collection techniques such as interviews, observation, and documentation. The findings reveal that the use of digital media at SD Negeri Kedawung II has enhanced the school’s visibility, strengthened communication with parents, and attracted public interest in the educational programs offered. The main challenges lie in the limited human resources and insufficient technological proficiency, which still need to be improved. Nevertheless, digital media has proven effective in strengthening the branding of public schools when managed consistently and professionally. This study recommends the establishment of a school digital promotion team, specialized training for content managers, and policy support from the local Department of Education.